Breaking the Grammar Barriers: A Descriptive Study of Indonesian EFL Learners’ Voices - Rozanah Katrina Herda; Kiki Juli Anggoro; Ana Mae M. Monteza; Nur Hidayanto Pancoro Setyo Putro; Maida Cinta Islami; Eko Wardoyo; Nunik Sugesti (Universitas Galuh, 2025)
Grammar plays a fundamental role in language learning, yet many students encounter challenges that hinder their mastery. These challenges can be categorized into cognitive, emotional, and instructional barriers, which impact learners' ability to engage with grammar effectively. This study investigates the dominant elements within these barriers and explores Indonesian university students' perceptions of grammar learning. Employing a quantitative descriptive design, this study used a five-point Likert-scale questionnaire of 28 items divided into four sections. The participants were 300 randomly selected university students majoring in English Education in Indonesia. The data were analyzed statistically using descriptive statistics, particularly mean scores, to determine trends and dominant elements. The findings revealed that in the cognitive barrier, the most dominant difficulties were applying grammar rules under pressure and needing more time to understand concepts. In the emotional barrier, the highest scores were related to anxiety when speaking and the belief that emotions affected learning. Regarding instructional barriers, students felt they needed more real-life practice and interactive, contextual lessons. Furthermore, the perception data indicated a generally positive attitude toward grammar learning, highlighting its importance and relevance. The study implies that teachers should address all dimensions to enhance grammar instruction and student success, aligning with the language and pedagogical innovation thrust and contributing to Sustainable Development Goal 4 (Quality Education).